THE DEVELOPMENT OF VIRTUAL VIDEO ANIMATED BASED ON ENGLISH TEACHING MEDIA FOR THE EIGHTH STUDENTS AT JUNIOR HIGH SCHOOL FITRA ABDI PALEMBANG - Eka Putri Lestari; Aswadi Jaya; Hermansyah (Universitas PGRI Palembang, 2024)
This research aims to develop virtual animated video-based teaching media to increase students' interest in learning and understanding in English teaching and learning activities in class VIII SMP Fitra Abdi Palembang. The method used in this research is research and development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Trials using a questionnaire showed that this media was very interesting with a percentage of 91.9% according to the attractiveness criteria. The results of the pre-test and post-test conducted on 30 students showed significant improvement. In the pre-test, only 7 students achieved scores according to the criteria for completeness of learning outcomes. After learning using virtual animated videos, 28 students achieved scores above the criteria for learning completeness (70), while 2 students were still below these criteria. The overall class avera1ge increased to 79.3. It can be concluded that virtual English video animation media is effective and successful in improving student learning outcomes and their interest in the learning process.